Oxidation of fish oil supplements in Australia. (4th July 2019) - Heller, Monique; Gemming, Luke; Tung, Chin; Grant, Ross
Abstract: Fish oils oxidise readily, forming primary and secondary oxidation products, which may be harmful for humans. Some recent studies reported that fish oil supplements in Australasia are oxidised above acceptable international limits, however other studies reported low levels of oxidation. This study employed peroxide and p-anisidine values determination to measure primary and secondary oxidation of fish oils in the Australian market. Of 26 supplements tested, 38% exceeded the limit for primary oxidation, 25% exceeded the limit for secondary oxidation and 33% exceeded the limit for total oxidation, according to international recommendations. Four specially marketed supplements were found to deliver significantly lower amounts of fish oil per capsule (165 vs. 577 mg, p = .007), yet cost significantly more on a per gram basis (2.97 vs 0.39, p < .001). However, there were no differences in any oxidative markers between regular supplements and the specially marketed products.